Contribuição ao conhecimento fitoquímico de ocotea gardneri (meisn) mez e ocotea duckei vattimo - Teles, Maria Madalena Rocha Silva (2016)
The Lauraceae family consists of about 70 genera and 2.500 species, with tropical and subtropical distribution. In Brazil, comprises 400 species in 25 genera. Among these, we highlight the Ocotea genus with about 350 species. This study aimed to carry out the phytochemical study Ocotea duckei Vattimo and Ocotea gardneri (Meisn) Mez, as well as to assess the antimicrobial activity and antileishman of isolated chemical constituents. For this, the plant material was subjected to extraction processes, partition and chromatography methods to isolate the chemical constituents. The chemical structures of the compounds were determined by spectroscopic methods and comparisons with literature data. Chromatographic fractionation of the dichloromethane phase Ocotea gardneri resulted in the isolation of triterpene 2,6,10,15,19,23-hexamethyl-2,6,10,14,18,22-tetracosahexeno (squalene) of 3, 4, 5 trimethoxybenzaldehyde and glycosylated sitosterol-3-O-β-D-glucopyranoside the ethyl acetate phase was isolated flavone steroid 3,5,7,3 ', 4'-pentaidroxiflavona (quercetin) and two flavonols 2- (3, 4-dihydroxyphenyl) -4H-chromene-3,5,7-triol (epicatechin) and 2- (3,4-dihydroxyphenyl) -4H-chromene-3,5,7-triol (epicatechin). All compounds are first reported in this species. To obtain the fraction of total alkaloids (FAT), the crude ethanolic extract of leaves of Ocotea duckei underwent alkaloid march and then the chromatographic fractionation, resulting in the isolation of reticulin and N- oxide reticulin alkaloid, which is reported for the first time in the genus. Further, the FAT was analyzed by LC-MS and GC-MS. LC-MS allowed the identification of reticulin alkaloids, coclaurina, discretamina, tetrahidrocolumbamina and N-oxide reticulin. The FAT analysis by GC-MS allowed the identification of metilreticulina metilcoclaurina and alkaloids. Of these alkaloids, only reticulin was identified to FAT leaves in previous studies. Flavonoids isolates were evaluated for antimicrobial activity by microdilution technique, compared to strains of S. mutans, P. aeruginosa and S. aureus. Quercetin presented a MIC of 83.5 mg / mL against S. aureus and catechin one MIC of 400 mg / mL against the P. aeruginosa. The reticulin alkaloids and reticulin N-oxide were subjected to MTT reduction method to evaluate the activity antileihmania front of L. amazonensis, and they did not show activity